Assessing the effectiveness of a community food security project for curriculum development. Issue 2 (3rd April 2019) - Krebs-Moberg, Julia; Ormsby, Alison
ABSTRACT: Many counties of Western North Carolina have high levels of food insecurity that may be addressed by training communities to grow, prepare, and preserve their own food. A curriculum was developed and tested in 2016 at a Section 8 housing development in Polk County, NC. Research investigated successful community agriculture projects and assessed participant learning. Weekly class evaluations were conducted, as well as pre- and post-surveys. Challenges included frustration over constraints enforced by the housing rules, poor soil, and unbearable Polk County heat. The final curriculum product can be applied to any community struggling with food security and community resiliency.